THE ROLE OF COMPUTED TOMOGRAPHY IN PATIENTS WITH GASTRIC CANCER IN RADIO-ONCOLOGICAL HOSPITAL - N. K. Silanteva; T. A. Agababian; V. Yu. Skoropad; O. G. Grishina (Сибирский онкологический журнал)
Background. Patients are referred to a specialized oncologic hospital with diagnosis of gastric cancer, which has been already established. Under this condition it is important to determine the clinical problems in which CT plays a crucial role. The aim of the study is the systematization of the major clinical challenges being addressed by CT in patients with gastric cancer treated at the radio-oncological hospital. Methods. A total 120 patients with gastric cancer at the different phases of combination therapy were included in our study: 91 patients underwent preoperative CT for the tumor staging; 70 patients underwent CT topometry; 40 patients were examined with CT in order to the post-therapy control. Results. The role of computed tomography in the study of gastric carcinoma is mainly represented by the staging of tumor according to the TNM system; CT topometry; assessment of response to neoadjuvant therapy; evaluation of postoperative complications and the post-therapy control. Conclusion. In a specialized hospital, CT plays a key role in the management of gastric cancer. CT has important impacts on clinical decisions and allows solving specific clinical problems.